The national security implications of solar geoengineering: an Australian perspective. Issue 5 (3rd September 2019) - Lockyer, Adam; Symons, Jonathan
ABSTRACT: Given current emissions trends an increase in global temperatures in excess of 2°C is highly likely in the coming century. In this context, it seems increasingly probable that states may consider solar geoengineering as a stop-gap climate response. Solar geoengineering refers to measures that aim to alleviate some measure of global warming by intentionally increasing the amount of the sun's energy that is reflected into space. Currently the two most discussed solar geoengineering techniques involve either marine cloud brightening or dispersing aerosols in the stratosphere. These techniques could be relatively inexpensive, are within the technological capacities (after a brief period of development) of technologically-advanced countries, and could have an almost immediate impact on temperatures. Yet, while solar geoengineering might potentially be utilised to manage some climate-linked security threats, it itself would create new security challenges. Consequently, this paper explores potential international security implications for Australia if a regional state, or group of states, initiates a solar geoengineering program. We conclude that since solar geoengineering is unlikely to become a first-order international issue, disputation over solar geoengineering will likely reflect, or act as a proxy for, wider patterns of state interaction. However, scenarios in which China and the United States take different positions, or in which there are divisions among regional powers, such as Indonesia, Malaysia, India and Singapore would pose the greatest threat to Australia's national security.